Pengaruh Variasi Tepung Tapioka Terhadap Tingkat kesukaan Bakso Ikan Bandeng (Channos channos Forsk) Presto - Tirani Pratiwi; Dini Nur Hakiki (Food Scientia : Journal of Food Science and Technology, 2021)
Modification of milkfish (Chanos chanos) by high pressure processing was done to increase added value and to develop new product innovations. One of the innovative products that can be developed is in the form of meatballs. The addition of milkfish into the manufacturing of meatballs is expected to produce meatballs with a distinctive aroma. The purpose of this study was to determine the effect of different variations of tapioca flour amount using organoleptic tests. The tests included testing of color, aroma, taste, and elasticity as well as testing the shelf-life of presto milkfish meatballs at room temperature. The experimental design used was Completely Randomized Design (CRD) with the scoring test method based on the level of consumer preference. The factors studied were the percentage of tapioca flour proportions to the raw material of presto milkfish which consisted of three treatments, namely P1 treatment 20 grams; P2 30 grams; P3 40 grams. Based on the results of the organoleptic test by 20 panelists, it can be concluded that the presto milkfish meatballs favored by the panelists are presto milkfish meatballs with milkfish: tapioca flour ratio 60 gr: 30 gr. Storage of the meatballs in room temperature at 24 hours cause discoloration.